Misuse of Forest Products Transport Documents - Ramadhan, Muhammad Alief Faizal; Asram, Asram; Rasyid, Wahyu (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This study examines the juridical review of the misuse of timber transport documents in Sidenreng Rappang Regency, with a case study of Decision Number 222/PID/B/LH/2023/PN Sdr.Purposes of the Research: The study aims to identify the forms of misuse of timber transport documents and analyze the judge's considerations in sentencing offenders involved in such misuse.Methods of the Research: The research employs a normative-empirical approach. The normative approach involves analyzing legal theories, principles, doctrines, and relevant regulations, such as Law No. 18 of 2013 on the Prevention and Eradication of Forest Destruction. The empirical approach is conducted through direct observation and interviews with judges at the Sidenreng Rappang District Court.Findings of the Research: The result reveal that the misuse of timber transport documents occurs when the documents used do not correspond to the actual physical condition of the transported timber, thereby violating applicable legal provisions. In Decision No. 222/PID/B/LH/2023/PN Sdr., the judge considered various factors, including aggravating and mitigating circumstances, before imposing a sentence of one year in prison and a fine of IDR 500,000,000. However, from the author's perspective, this decision requires further review, considering the possible involvement of other parties in this criminal act.